Choice way of closing a wound in the abdominal wall complex surgical treatment of peritonitis prevalence - V. M. Bensman; Y. P. Savchenko; S. N. Scherba; V. A. Avakymian; S. N. Pyatakov; I. V. Golikov; A. S. Saakyan; K. V. Triandafilov; E. A. Saakyan (Кубанский научный медицинский вестник, 2015)
It studied 764 patients with widespread peritonitis shows the benefits of treatment relaparotomy-programmed with the closing of the surgical wound with removable draining musculoaponeurotic seams (RDMAS). In the case of intra-abdominal pressure normalization performed laparotomic closing the wound using RDMAS, and at its persistent increase -only skin sutures. This proved a significant decrease in mortality. For large defects of the abdominal wall, in the case where the conventional surgical wound closure of sutures is impossible, it is permissible use of fabric tensor, and free shaded plastic skin flaps.